SCULPTURE3D, du projet de laboratoire à l’exposition numérique - Marion Boudon-Machuel; Barthélemy Serres (In Situ)
The SCULPTURE3D research project is a collaborative and multidisciplinary laboratory experiment financed by the Centre-Val de Loire region between 2014 and 2018, which aims to explore what 3D brings to the study of sculpture and to interpret the region’s heritage of sculptures from the Renaissance Era. It is an association between researchers from the University of Tours, working with the Centre d’études supérieures de la Renaissance (CESR) and with the Fundamental and Applied Computer Science of Tours (LIFAT), and various heritage institutions (DRAC Centre, Museum of Fine Arts of Tours, CMN, Château de Blois…) as well as a team of experts on innovative softwares (CETU ILIAD3), and the new small business Kulturae’com, two innovative entities who got their start through that project. The thirty digital objects created with the help of a 3D optical scanner is the first key part of a virtual museum of 3D sculptures from the Renaissance Era in the Val de Loire, intended both for researchers and the general public. Similarly, the Sculpturoscope, la Vierge à l’Enfant du réel au virtuel meta-exposition (at the Museum of Fine Arts of Tours, from May 25th to September 10th 2018) made the results of scientific research available to the general public by using digital medias as both a tool of investigation and mediation.